ANALISIS KUALITAS PELAYANAN PUBLIK DI BANDAR UDARA RADIN INTEN II PROVINSI LAMPUNG - Ade Iskandar; Fitri Stella Arisafitri (Universitas Bandar Lampung (UBL), 2018)
Service quality and customer satisfaction are inseparable. Either service quality or customer satisfaction mostly can be measured by comparing perceived performance of the institution providing the service and the expectation of the service itself. Customer satisfaction rises when the performance is higher than the expectation. In the contrary, higher expectation rather than the performance shows users’ dissatisfaction which also shows the real description of the service quality. Radin Inten II Airport has been established as Public Service Agency. Therefore it is important to carry out some researches to discover service quality provided by the institution. Analyzed by Gap Analysis, Level of Satisfaction Analysis and Importance-Performance Analysis, this research figures the picture of service quality through five dimensions, Reliability, Responsiveness, Assurance, Empathy and Tangibles. The result of the research shows there are four indicators in Quadrant A that the institution must focus on, in order to increase the service quality, four indicators in Quadrant B, two indicators in Quadrant C and six indicators in Quadrant D. There are no indicators, of sixteen indicators being analyzed in the research, which its performance score exceeds its expectation score so it is obvious to say that there are dissatisfaction regarding services provided by the institution.